ANALISIS PROGRAM MAGANG DALAM PENGEMBANGAN SOFT SKILL MAHASISWA TEKNOLOGI PENDIDIKAN UNIVERSITAS NEGERI MAKASSAR - Meriati Lembang Bulawan; Citra Rosalyn Anwar; Abdul Hakim (STKIP Subang, 2026)
This study analyzes the internship program's role in developing the soft skills of Educational Technology students at Universitas Negeri Makassar, particularly within non-educational sectors. The research is prompted by the dynamic demands of the global job market, which increasingly prioritize soft skills alongside technical expertise, and the necessity for graduates to bridge the gap between academic theory and professional practice. The primary objective is to evaluate the program's implementation, examine the resulting soft skill enhancements, and identify obstacles faced by students. A qualitative research methodology was employed, utilizing the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through in-depth interviews and documentation involving students and faculty members. The results demonstrate that the internship program significantly contributes to the development of essential soft skills, including critical thinking, communication, collaboration, and creativity (4Cs), as well as responsibility and adaptability. Furthermore, the findings reveal that Educational Technology students have extensive career opportunities in diverse industries such as media, government, and creative sectors due to their flexible, multidisciplinary competencies. However, students encountered challenges such as technical skill gaps specifically in digital tool proficiency and differences between academic and corporate standards. In conclusion, the program serves as a strategic bridge that enhances graduate readiness and professional competence in a competitive workforce.